2015
DOI: 10.1007/s10552-015-0697-y
|View full text |Cite
|
Sign up to set email alerts
|

Understanding rural–urban differences in risk factors for breast cancer in an Indian population

Abstract: Differences in the prevalence of central adiposity and age at first full-term pregnancy between rural and urban women from India may explain some differences in breast cancer rates between these two populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…In India, BC incidence is rising more in urban women compared to rural women. A study done on women residing in urban areas in Mumbai, India reported that the waist to hip ratio and late age of first child delivery in urban women compared to rural women were key factors responsible for BC to occur more in urban women [12]. Gupta A. et al showed in their study that there is very poor awareness among Indian women irrespective of their socioeconomic status with regard to BC symptoms and early detection [13].…”
Section: Discussionmentioning
confidence: 99%
“…In India, BC incidence is rising more in urban women compared to rural women. A study done on women residing in urban areas in Mumbai, India reported that the waist to hip ratio and late age of first child delivery in urban women compared to rural women were key factors responsible for BC to occur more in urban women [12]. Gupta A. et al showed in their study that there is very poor awareness among Indian women irrespective of their socioeconomic status with regard to BC symptoms and early detection [13].…”
Section: Discussionmentioning
confidence: 99%
“…Living in rural areas decreases the risk for breast carcinoma as compared to urban counterparts mainly due their adherence to rural lifestyle . Waist‐to‐hip ratio of ≥0.95 compared to ratio ≤0.84 was found strongly associated with risk of BC in both rural and urban populations (OR urban = 4.10, 95% CI, 3.03–5.56; OR rural = 3.01, 95% CI, 1.85‐4.90) . Though increased anthropometric measures like larger body size and obesity determines breast cancer risk in India however it does not contribute appreciably to the urban–rural breast cancer differences .…”
Section: Methodsmentioning
confidence: 96%
“…The details of anthropometric measurements have been explained earlier [7] . WHR was calculated as waist circumference (WC) (in cm) divided by hip circumference (HC) (in cm) and grouped into three categories.…”
Section: Methodsmentioning
confidence: 99%